Strategic concepts as micro-level tools in strategic sensemaking - Jalonen, Kari; Schildt, Henri; Vaara, Eero (Strategic management journal, 2018)
Research summary: The purpose of this article is to illuminate the role of concepts in strategic sensemaking. Based on a longitudinal real-time study of a city organization, we demonstrate how the concept of "selfresponsibility" played a crucial role in strategic sensemaking. We develop a theoretical model that elucidates how strategic concepts are used in meaning-making, and how such concepts may be mobilized for the legitimation of strategic change. Our main contribution is to offer strategic concepts as a missing micro-level component of the language-based view of strategic processes and practices. By so doing, our analysis also adds to studies on strategic ambiguity and advances research on vocabularies. Managerial summary: Our analysis helps to understand the role of strategic concepts, that is, specific words or phrases with established and at least partly shared meanings, in an organization's strategy process. We show how adopting the concept "self-responsibility" helped managers in a city organization to make sense of environmental challenges and to promote change. Our analysis highlights how such concepts involve ambiguity that can help managers to establish common ground, but can also hinder implementation of specific decisions and actions if it grows over time. We suggest that under environmental changes, development of new strategic concepts may be crucial in helping managers to collectively deal with environmental changes and to articulate a new strategic direction for the organization.